Penerapan Model Pembelajaran Complete Sentence dalam Meningkatkan Hasil Belajar Bahasa Indonesia Siswa Kelas IV SD Katolik 2 St. Joseph Woloan - Steven Mandey (Jurnal Ilmiah Wahana Pendidikan, 2023)
In learning Indonesian at the elementary level of education, there are four basic skills that must be owned by the learners, namely; listening, writing, reading and speaking skills that are the foundation of skills that can also be implemented in other fields or subjects. This study is aimed at improving one of the language skills of reading. What is done in the fourth grade of St. Catholic 2 St. Joseph Woloan who has a total of 17 students. The purpose of this research is to improve students' skill especially reading skill by applying one of cooperative learning model that is Complete Sentence. This model emphasizes the completeness of sentences through stories they have read before that can be done through the form of group discussions. This research applies classroom action research methods that include stages; planning, execution, observation and reflection, then the four stages are referred to as a cycle of activity and in this study activities are carried out in two cycles to obtain more accurate data from the first cycle and second cycle. Classically the result of the first cycle achievement was 68.82% and in the second cycle increased to 87.05%. From the results of data analysts obtained shows that the improvement of learning outcomes of Indonesian students through the use of Complete Sentence learning model has increased significantly.